2004
DOI: 10.1128/jvi.78.20.11360-11370.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Proteomic Analysis of Thirty-Nine Structural Proteins of Shrimp White Spot Syndrome Virus

Abstract: White spot syndrome virus (WSSV) virions were purified from the hemolymph of experimentally infected crayfish Procambarus clarkii, and their proteins were separated by 8 to 18% gradient sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDS-PAGE) to give a protein profile. The visible bands were then excised from the gel, and following trypsin digestion of the reduced and alkylated WSSV proteins in the bands, the peptide sequence of each fragment was determined by liquid chromatography-nano-electrospray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
166
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(184 citation statements)
references
References 56 publications
16
166
0
2
Order By: Relevance
“…In contrast, the responses of shrimp to YHV infection at the molecular level are currently poorly described. WSSV is an enveloped, ellipsoid and large double-stranded DNA virus (5), while YHV is an enveloped, rod-shaped and single-stranded RNA virus (6). As YHV contains a single-stranded RNA genome, the molecular basis for shrimp response to YHV might be somewhat different than that to the DNA virus WSSV.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the responses of shrimp to YHV infection at the molecular level are currently poorly described. WSSV is an enveloped, ellipsoid and large double-stranded DNA virus (5), while YHV is an enveloped, rod-shaped and single-stranded RNA virus (6). As YHV contains a single-stranded RNA genome, the molecular basis for shrimp response to YHV might be somewhat different than that to the DNA virus WSSV.…”
Section: Introductionmentioning
confidence: 99%
“…The Western blot result was in accord with SDS-PAGE analysis, which confirmed that band 5 of the SDS-PAGE gel was derived from GCReV-109 virions and corresponded to the VP33 protein. We therefore conclude that VP33 is a major structural protein of GCReV-109 virions [27][28][29].…”
Section: Vp33 Is a Structural Protein Of Gcrev-109mentioning
confidence: 68%
“…The ORF WSSV388 encodes a putative 786 amino acid protein (88 kDa). A recent proteomic analysis (Tsai et al, 2004) confirms the existence of this protein which was named VP75 based on its migration in an SDS-PAGE. PROSITE database analysis indicated that WSSV388 contained a putative immunoglobulin/major histocompatibility complex (IG MHC) protein signature motif.…”
Section: Discussionmentioning
confidence: 89%
“…Only a few major structural proteins (Van Hulten et al, 2000a,b;Chen et al, 2002;Zhang et al, 2002) and enzymes (Tsai et al, 2000;Li et al, 2004) date. SDS-PAGE and 2-D electrophoresis were combined with mass spectrometry, which led to the successful identification of new structural proteins that have been used to study the WSSV proteome Tsai et al, 2004;Zhang et al, 2004). However, the role of most of these viral proteins and the molecular mechanism of infection are still not known.…”
Section: Introductionmentioning
confidence: 99%